Ketepatan Putusan Bebas No. 36/Pid.Sus/2023/PN Lbb dalam Perkara Tindak Pidana Incest - Harahap, Rizky Olivia Kartina; Sitepu, Rajin (Legal Standing : Jurnal Ilmu Hukum, 2024)
This study aims to determine whether the Acquittal Verdict No. 36/Pid.Sus/2023/PN Lbb in the Incest Crime Case is appropriate or not. The method used is normative juridical. Data was obtained by reviewing library materials such as books, journals, and references related to the Lubuk Basung District Court Verdict No. 36/Pid.Sus/2023/PN Lbb. The results of the study on Verdict 36/Pid.Sus/2023/PN Lbb, the defendant was charged with committing the crime of incest according to "Article 82 paragraph (2) in conjunction with Article 76E of Law No. 35 of 2014". The evidence presented, including witness statements, mostly in the form of testimonium de auditu, was not strong enough. There were no witnesses who directly supervised the defendant, and there was a discrepancy in the statement of the time of the incident, the post-mortem evidence only showed the victim's physical condition without linking the act to the defendant. The judge decided that the charges could not be proven legally and convincingly, so the defendant was declared free from all charges. This decision emphasizes the importance of strong and consistent evidence in criminal trials.